2016
DOI: 10.1097/igc.0000000000000711
|View full text |Cite
|
Sign up to set email alerts
|

miR-375 Affects the Proliferation, Invasion, and Apoptosis of HPV16-Positive Human Cervical Cancer Cells by Targeting IGF-1R

Abstract: miR-375 plays an important role in the tumorigenesis and development of cervical cancer. IGF-1R might represent a target gene of miR-375 in cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…3A. Although IGF-1R has been identified as a direct target of miR-375 in laryngeal squamous cell cancer and cervical cancer [18, 19], whether miR-375 targets IGF-1R to function in OSCC cells is unclear. First, the dual-luciferase reporter assay was performed and the luciferase activity was determined (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A. Although IGF-1R has been identified as a direct target of miR-375 in laryngeal squamous cell cancer and cervical cancer [18, 19], whether miR-375 targets IGF-1R to function in OSCC cells is unclear. First, the dual-luciferase reporter assay was performed and the luciferase activity was determined (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By bioinformatics, IGF-1R gene was identified as a potential target of miR-375. In laryngeal squamous cell cancer and cervical cancer, IGF-1R has been testified as a functional target of miR-375 [18, 19]. IGF-1R belongs to the insulin receptor (IR) family which includes the IR, IGF-1R, IGF-1R/IR, and IGF-2R.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Some other miRNAs, such as miR-139, miR-634, miR-375 and miR-125, were also recently found to be dysregulating in cervical cancer. [11][12][13][14] They modulated behaviors of cervical cancer cells, including proliferation, apoptosis, invasion, radio sensitivity and drug sensitivity, via posttranscriptional suppression of oncogenes Nin one binding protein (NOB1), mammalian target of rapamycin complex 1 (mTOR), signal transducer and activator of transcription 3 (STAT3), and insulin-like growth factor 1 receptor (IGF-1R).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of endogenous and small noncoding RNAs with 21–23 ribonucleotides, which can induce mRNA degradation or act as repressors of translation through directly binding to a target site in the 3′‐untranslated regions of their target genes. Existing studies found that miRNA mediated gene regulation involved in multiple pathological processes including cell proliferation, differentiation, migration, survival, and tumorigenesis . Recent evidence has shown that miRNAs also plays a vital role in chemotherapeutic resistance.…”
Section: Introductionmentioning
confidence: 99%